Compression-resistant and stretch-resistant low-sheet-resistance self-healing flexible transparent conductive film and manufacturing method thereof
By using electric field drive and scraping technology to fill the conductive material in the flexible transparent conductive film, a self-healing conductive film with a grid interconnected structure is solved, and the existing conductive film is prone to cracks under pressure and tensile conditions is achieved, and the combination of high conductivity and transparency is achieved, which is suitable for the field of flexible electronics.
Patent Information
- Application Number
- CN202510408989.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing flexible transparent conductive films are prone to cracks under pressure and tensile conditions, affecting the conductive properties, and the manufacturing process is complex, which limits large-area manufacturing and widespread application.
The conductive paste is driven by an electric field to fill the pre-imprinted grid interconnection groove with conductive material, solidified to form a solid conductive layer, and then scraped coating to fill the liquid conductive material to form an upper liquid conductive layer, and finally spin-coated flexible substrate material packaging to realize the preparation of the conductive film.
It realizes the self-healing of the conductive film without delay under pressure and tensile conditions, maintains low square resistance and high conductivity, and has a simple process and adjustable transparency, which meets the needs of the flexible electronics field.
Smart Images

Figure CN119905291A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of micro-nano manufacturing technology, and particularly relates to a compression-resistant and stretch-resistant low-square-resistance self-healing flexible transparent conductive film and a manufacturing method thereof. Background Art
[0002] The flexible electronics industry is developing rapidly, and flexible electronic products such as flexible displays, flexible solar cells, and flexible sensors are flooding the market. In many application scenarios, the core components of the product need to have good conductivity to achieve efficient transmission of electrical signals, and at the same time require high light transmittance to meet the visibility requirements of display screens, touch panels, etc. Therefore, flexible transparent conductive films that are flexible, highly transparent, and highly conductive are the core of the development of many flexible optoelectronic products, and the manufacture of flexible transparent conductive films has become a key issue that cannot be underestimated in the field of flexible electronics.
[0003] Traditional conductive films, such as metal films, have excellent conductivity, but they have disadvantages such as high rigidity and opacity, making it difficult to adapt to the needs of emerging flexible electronic devices. In addition, indium tin oxide (ITO) is the most widely used. ITO not only has excellent conductivity and high visible light transmittance, but also its film forming technology and subsequent etching patterning process system are mature and reliable. It is the mainstream material for the current development of transparent conductive films. However, ITO transparent conductive film is a brittle material and is prone to brittle cracking when subjected to force. Therefore, the development of flexible transparent conductive films with good mechanical bending properties has become a research hotspot.
[0004] Although flexible conductive films have promoted the development and application of flexible electronic skin and flexible displays to a certain extent, in actual application, flexible electronic devices are often squeezed, collided, scratched, and collided, which makes it difficult to avoid mechanical damage such as cracks on the conductive film, affecting the conductive performance. In view of this, the internal self-healing property of the conductive film becomes the key to solving this problem. This property means that the conductive film can self-heal without delay after being damaged, maintain low square resistance, and ensure the continuous transmission of electrical signals. Therefore, the internal self-healing of the conductive film has become a hot topic in current research. At present, the manufacturing process system of flexible transparent conductive films also presents a diversified trend, covering a variety of technologies such as electrospinning, magnetron sputtering, and vapor deposition; however, they all face complex process technology and high equipment costs, which limit the large-scale manufacturing and wide application of flexible transparent conductive films.
[0005] In summary, the current flexible electronics industry has an extremely urgent need for high-performance conductive films, but there are many problems with existing materials and processes. Therefore, it is urgent to develop a low-resistance self-healing flexible transparent conductive film that is resistant to compression and tension, which can achieve internal self-healing without delay under pressure and tension conditions and maintain low resistance. This conductive film is expected to break the limitations of existing flexible devices, open up a new development path for the flexible electronics industry, and meet the urgent demand for high-performance conductive films in multiple fields from foldable mobile phones, smart wearable devices to flexible sensor devices.
[0006] The invention patent application with publication number CN107527675A discloses a flexible conductive film and a preparation method thereof, including a conductive layer and a liquid metal layer covering the conductive layer, wherein the conductive layer is a carbon nanotube layer, a metal conductive layer or a metal oxide conductive layer. When the conductive layer is a damaged or defective conductive layer, the liquid metal has fluidity and can repair the damage of the conductive layer. According to the invention, the liquid metal layer is directly coated on the conductive layer, which does not have the characteristic of adjusting transparency, and the preparation process is conventional spraying, and the process performance has the problem of unstable. Summary of the invention
[0007] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a low-square-resistance self-healing flexible transparent conductive film and a manufacturing method that are resistant to compression and tension. The conductive slurry is filled into the pre-embossed grid interconnection grooves by an electric field, and the conductive slurry is solidified to form a solid conductive layer. The liquid conductive slurry is then filled by scraping to form an upper liquid conductive layer. Finally, the flexible base material is spin-coated to encapsulate and complete the preparation of the conductive film. This film, which is a composite of upper and lower conductive materials, has an upper layer that can self-heal and fill the microcracks of the lower layer without delay due to its fluidity, maintains stable conduction, has good compressive resistance and stretchability, and at the same time, the transparency of the film can be flexibly adjusted by controlling the size of the grooves, and has the advantages of high conductivity, stronger environmental adaptability and longer life.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: A low-square-resistance self-healing flexible transparent conductive film that is resistant to compression and stretching comprises a flexible substrate. The surface of the flexible substrate has grooves interconnected by micro-nanoscale grids. The grooves are filled with two layers of conductive materials. The lower layer is a solid conductive layer formed by conductive materials, and the upper layer is a liquid conductive material. The liquid conductive material and the solid conductive layer can coexist stably. When microcracks are generated in the solid conductive layer of the lower layer under various external deformations, the liquid conductive material of the upper layer can self-heal and fill the microcracks generated in the solid conductive layer without delay due to its fluidity to maintain stable conduction. An encapsulation layer is provided on the surface of the groove.
[0009] The material of the flexible substrate includes polydimethylsiloxane, polyimide or polyester.
[0010] The conductive material includes gold, silver paste, or metal nanowire / carbon-based flexible polymer doped with metal nanowires.
[0011] The liquid conductive material is liquid metal or liquid conductive gel, and the liquid metal includes gallium indium tin alloy.
[0012] The method for manufacturing a compression-resistant and stretch-resistant low-square-resistance self-healing flexible transparent conductive film comprises the following steps: The first step is to prepare the nanoimprint mold and the flexible substrate: use photolithography to prepare an imprint mold with a micro-nanoscale grid interconnected structure with surface protrusions; spin-coat to generate a flexible substrate material with a thickness of micrometers, and place a conductive substrate under the flexible substrate material; The second step is to prepare a micro-nanoscale grid interconnected groove structure: press the imprint mold onto the flexible substrate material, dry and completely cure the flexible substrate material, then peel off the imprint mold to obtain a flexible substrate with micro-nanoscale grid interconnected grooves; The third step is to prepare a solid conductive layer: under the assistance of an electric field force, fill the groove of the flexible substrate with a conductive material and solidify it to form a solid conductive layer; Step 4: Preparation of a liquid conductive layer: Filling the solid conductive layer in the groove with liquid conductive material again by scraping to form a liquid conductive layer; The fifth step is encapsulation: using spin coating, a transparent encapsulation layer is generated on the surface of the liquid conductive material, and the upper liquid conductive material is encapsulated in the groove to complete the preparation and encapsulation of the self-healing flexible transparent conductive film.
[0013] The grooves interconnected by the micro-nano scale grid can adjust the line width and arrangement of the grooves to achieve regulation of the transparency of the conductive film.
[0014] The third step is specifically as follows: injecting liquid conductive material into the conductive nozzle, connecting alternating current between the conductive substrate and the conductive nozzle, allowing the electric field force to act, and filling the conductive material into the groove of the flexible substrate, moving the conductive nozzle, controlling the filling amount of the conductive material, ensuring that the conductive material is filled into other predetermined groove positions, heating and drying it to solidify, and completing the preparation of the solid conductive layer.
[0015] The thickness of the solid conductive layer is 5-50 μm.
[0016] The liquid conductive material is scraped to a thickness of 5-50 μm.
[0017] The transparent encapsulation layer is made of PDMS material and has a thickness of 20-80 μm.
[0018] The flexible substrate material includes polydimethylsiloxane, polyimide or polyester.
[0019] The imprinting mold is a silicon wafer having a protruding structure after etching.
[0020] The conductive substrate is a rigid substrate glass with conductive nanomaterials deposited on the surface, and the conductive nanomaterials include indium tin oxide or gold.
[0021] The conductive material includes gold, silver paste, or metal nanowire / carbon-based flexible polymer doped with metal nanowires.
[0022] The liquid conductive material is liquid metal or liquid conductive gel, and the liquid metal includes gallium indium tin alloy.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The surface of the flexible substrate of the present invention has a micro-nanoscale grid interconnected groove structure. By adjusting the line width and arrangement of the protruding structure of the nanoimprint mold, such as the density, the size of the grid interconnected grooves of the flexible substrate can be flexibly adjusted to ensure the transparency of the conductive film.
[0024] (2) If microcracks are generated in the lower solid conductive layer of the present invention due to external influences, the liquid conductive material disposed on the upper layer has fluidity and can heal and fill the microcracks generated in the solid conductive layer 7 without delay to maintain stable conduction.
[0025] (3) In the preparation of the solid conductive layer, the conductive slurry is filled into the groove of the flexible substrate with the assistance of an electric field force, and solidified to form a solid conductive layer. The advantage or principle of the electric field force is that liquid conductive materials usually have a high surface energy, and thus cannot be completely filled into the micro-nano scale grid grooves. With the assistance of the electric field force, the liquid conductive material can be completely filled into the micro-nano scale grooves; thus, the process is simple and ingenious.
[0026] In summary, the present invention adjusts the transparency of the conductive film by changing the groove line width and arrangement of the surface of the imprinting mold; under external pressure and stretching, the lower solid conductive material produces microcracks, and the upper liquid conductive material fills the microcracks caused by large stress without delay and self-healing due to its strong fluidity to maintain low square resistance, thereby achieving high conductivity; during preparation, the electric scraping method can achieve the perfect filling of high surface energy liquid conductive materials into the grooves of the micro-nano grid structure, and realize the large-area scraping forming of the transparent conductive film structure. Therefore, the present invention has simple process and strong operability, and the obtained conductive film has high conductivity, high transmittance, and compressible and stretchable properties, which expands the application prospects of conductive films in the field of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of the imprinting mold and the flexible substrate.
[0028] Figure 2Schematic diagram of the process of nanoimprinting grooves on a flexible substrate.
[0029] Figure 3 It is a schematic diagram of the structure of a flexible substrate with a groove structure and a conductive substrate.
[0030] Figure 4 Schematic diagram of the filling process of the lower solid conductive layer slurry.
[0031] Figure 5 This is a schematic diagram of the structure after the lower layer of solid conductive material is solidified.
[0032] Figure 6 Schematic diagram of the filling process of the upper layer of liquid conductive material.
[0033] Figure 7 Schematic diagram of the structure after the upper layer of liquid conductive material is filled.
[0034] Figure 8 This is a schematic diagram of the structure after the conductive film packaging is completed.
[0035] Fig. 9 It is a schematic diagram of the working mechanism of the present invention under pressure and tension conditions.
[0036] Fig.10 It is a schematic diagram of the three-dimensional structure of the product prepared by the present invention.
[0037] Fig.11 It is a schematic diagram comparing the compressive performance of the present invention and a common conductive film.
[0038] In the figure: flexible base material 1; imprinting mold 2; groove 2'; conductive substrate 3; flexible base 4; conductive nozzle 5; conductive material 6; solid conductive layer 7; scraper 8; liquid conductive material 9. DETAILED DESCRIPTION
[0039] The preparation process of the present invention will be described in detail below with reference to the schematic diagram.
[0040] Reference Figure 3-Figure 8 , including a flexible substrate 4, the surface of the flexible substrate 4 has grooves 2' interconnected by micro-nano scale grids, and the line width and arrangement of the grooves 2', such as the density, are adjusted to achieve flexible regulation of the size of the grid interconnected grooves of the flexible substrate, thereby ensuring the transparency of the conductive film; the grooves 2' are filled with two layers of conductive material, the lower layer is a solid conductive layer 7 formed by a conductive material 6, and the upper layer is a liquid conductive material 9, the liquid conductive material 9 and the solid conductive layer 7 can coexist stably for a long time, when the solid conductive layer 7 of the lower layer generates microcracks under various deformations such as external impact, stretching, torsion, folding, etc., the liquid conductive material 9 of the upper layer can heal the microcracks generated by the solid conductive layer 7 without delay due to its fluidity to maintain stable conduction, and an encapsulation layer is provided on the surface of the groove 2'.
[0041] The material of the flexible substrate 4 includes polydimethylsiloxane, polyimide or polyester.
[0042] The conductive material 6 includes gold or silver paste, or a flexible polymer doped with metal nanowires / carbon, or liquid metal; the liquid metal includes bismuth indium tin alloy.
[0043] The liquid conductive material 9 is liquid metal or liquid conductive gel, and the liquid metal includes gallium indium tin alloy.
[0044] The method for manufacturing a compression-resistant and stretch-resistant low-square-resistance self-healing flexible transparent conductive film comprises the following steps: Step 1: Preparation of nanoimprint mold and flexible substrate: Figure 1 As shown, an imprinting mold 2 with a micro-nanoscale grid interconnected structure with surface protrusions is prepared by photolithography and etching technology; low surface energy treatment is performed to facilitate demolding after subsequent imprinting is completed; a layer of flexible base material 1 with a thickness of micrometer level is spin-coated by a glue spreader, and a conductive substrate 3 is placed under the flexible base material 1. The conductive substrate 3 is a rigid substrate glass with conductive nanomaterials deposited on the surface, and the conductive nanomaterials are indium tin oxide or gold.
[0045] Step 2: Preparation of micro-nanoscale grid interconnected groove structure: Figure 2 As shown, an imprinting mold 2 treated with low surface energy is pressed onto a flexible substrate material 1 with a certain pressure, wherein the imprinting mold 2 is a silicon wafer having a protruding structure after etching; an oven is used to adjust the ambient temperature to a temperature condition under which the flexible substrate material 1 can be cured; after the flexible substrate material 1 is completely cured, the imprinting mold 2 is peeled off to obtain a flexible substrate 4 having micro-nanoscale grid interconnected grooves, as shown in FIG. Figure 3 shown.
[0046] Step 3: Preparation of solid conductive layer: Figure 4 As shown, a liquid silver paste is prepared in advance as the conductive material 6, and is injected into the storage cavity of the conductive nozzle 5. An alternating current is connected between the conductive substrate 3 and the conductive nozzle 5. At this time, the electric field force takes effect, and the conductive material 6 is filled into the groove 2' of the flexible substrate 4. At the same time, the conductive nozzle 5 is moved to control the filling amount of the conductive material 6 to ensure that the conductive material 6 can be accurately and efficiently filled into other predetermined grooves 2' positions. After filling, it is heated and dried to be solidified to complete the preparation of the solid conductive layer 7. The thickness of the solid conductive layer is 40μm. Figure 5 shown.
[0047] Step 4: Preparation of liquid conductive layer: Figure 6As shown, a liquid conductive layer is prepared by scraping, and a liquid conductive material 9 is directly scraped on the solidified conductive material layer 7 with a scraper 8, and filled into the upper layer of the groove 2' of the flexible substrate 4. After the filling is completed, the residual material on the surface of the flexible substrate is wiped off to form a liquid conductive layer. The scraping thickness of the liquid conductive material 9 is 40μm, and the liquid conductive material 9 is a gallium indium tin alloy, such as Figure 7 shown.
[0048] Step 5: Encapsulation: After the filling of the upper and lower conductive materials is completed, the flexible base material is spin-coated on the surface of the film. By controlling the rotation speed of the spin coating, a transparent encapsulation layer with a thickness of 30 μm is generated, and the upper liquid conductive material 9 is encapsulated in the groove to complete the preparation and encapsulation of the self-healing flexible transparent conductive film. Figure 8 shown.
[0049] The self-healing flexible transparent conductive film obtained by the present invention has good conductive stability; the composite form of the upper and lower conductive materials has good compressive resistance and stretchability. Fig. 9 As shown, when external pressure and tension act on the conductive film, microcracks are generated in the lower solid conductive layer 7, and the upper liquid conductive material 9 heals and fills the cracks without delay to maintain stable conduction; Fig.10 As shown, it is a three-dimensional schematic diagram of the prepared transparent conductive film. The grooves interconnected by the micro-nano scale grid on the flexible substrate 4 are filled with upper and lower layers of different conductive materials. The transmittance of the conductive film can be adjusted by regulating the size and arrangement of the grooves.
[0050] Reference Fig.11 As can be seen from the figure, the self-healing flexible transparent conductive film of the present invention has stronger compressive resistance than ordinary conductive films. The resistance of ordinary conductive films increases sharply under 5.1 MPa, while the structure of the present invention increases the compressive resistance to 17.5 MPa.
Claims
1. A low-resistance self-healing flexible transparent conductive film that is resistant to compression and tension, characterized in that: The invention comprises a flexible substrate (4), wherein the surface of the flexible substrate (4) has grooves (2') interconnected by micro-nanoscale grids, wherein the grooves (2') are filled with two layers of conductive materials, wherein the lower layer is a solid conductive layer (7) formed by a conductive material (6), and the upper layer is a liquid conductive material (9), wherein the liquid conductive material (9) and the solid conductive layer (7) can coexist stably, and when microcracks are generated in the solid conductive layer (7) under various external deformations, the liquid conductive material (9) in the upper layer can heal the microcracks generated by the solid conductive layer (7) without delay and maintain stable conduction due to its fluidity, and an encapsulation layer is provided on the surface of the groove (2').
2. The compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 1, characterized in that: The material of the flexible substrate (4) includes polydimethylsiloxane, polyimide or polyester.
3. The compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 1, characterized in that: The conductive material (6) includes gold or silver paste, or a metal nanowire / carbon-based flexible polymer doped therein.
4. The compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 1, characterized in that: The liquid conductive material (9) is liquid metal or liquid conductive gel, and the liquid metal includes a gallium-indium-tin alloy.
5. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of nanoimprint mold and flexible substrate: using photolithography technology to prepare an imprint mold (2) with a surface protruding micro-nanoscale grid interconnected structure; spin coating to generate a flexible substrate material (1) with a thickness of micrometer level, and placing a conductive substrate (3) under the flexible substrate material (1); Step 2: Preparation of a micro-nanoscale grid interconnected groove structure; pressing an imprinting mold (2) onto a flexible substrate material (1), drying and completely curing the flexible substrate material (1), and then peeling off the imprinting mold (2) to obtain a flexible substrate (4) having micro-nanoscale grid interconnected grooves; Step 3: Preparation of a solid conductive layer (7); under the assistance of an electric field force, the conductive material (6) is filled into the groove (2') of the flexible substrate (4), and solidified to form a solid conductive layer (7); Step 4: Preparation of a liquid conductive layer; using a scraping method, the liquid conductive material (9) is again filled onto the solid conductive layer (7) in the groove (2') to form a liquid conductive layer; Step 5: Encapsulation: Using a spin coating method, a transparent encapsulation layer is formed on the surface of the liquid conductive material (9), and the upper layer of the liquid conductive material (9) is encapsulated in the groove (2'), thereby completing the preparation and encapsulation of the self-healing flexible transparent conductive film.
6. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 5, characterized in that: The micro-nanoscale grid-interconnected grooves (2') are used to adjust the line width and arrangement of the grooves (2') to achieve regulation of the transparency of the conductive film.
7. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 5, characterized in that: The third step specifically comprises: injecting liquid conductive material (6) into the conductive nozzle (5), connecting alternating current between the conductive substrate (3) and the conductive nozzle (5), causing the electric field force to act, and filling the conductive material (6) into the groove (2') of the flexible substrate (4), moving the conductive nozzle (5), controlling the filling amount of the conductive material (6), ensuring that the conductive material (6) is filled into other predetermined groove (2') positions, heating and drying to solidify it, and completing the preparation of the solid conductive layer (7).
8. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 5, characterized in that: The thickness of the solid conductive layer (7) is 5-50 μm; The coating thickness of the liquid conductive material (9) is 5-50 μm.
9. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 5, characterized in that: The imprinting mold (2) is a silicon wafer having a convex structure after etching; The conductive substrate (3) is a rigid substrate glass with conductive nanomaterials deposited on the surface, and the conductive nanomaterials include indium tin oxide or gold.
10. The method for manufacturing a compression- and tension-resistant low-square-resistance self-healing flexible transparent conductive film according to claim 5, characterized in that: The flexible substrate material (1) comprises polydimethylsiloxane, polyimide or polyester; The transparent encapsulation layer is made of PDMS and has a thickness of 20-80 μm; The conductive material (6) includes gold or silver paste, or a flexible polymer doped with metal nanowires / carbon; The liquid conductive material (9) is liquid metal or liquid conductive gel, and the liquid metal includes a gallium-indium-tin alloy.
Citation Information
Patent Citations
Semiconductor structure and forming method thereof
CN106252247A
Flexible conductive film and preparation method thereof
CN107527675A
Transparent electromagnetic shielding film structure and preparation method thereof
CN109922645A
Novel conductive film and manufacturing method thereof
CN113161039A
Conductive film and preparation method thereof, touch panel, display device and electronic equipment
CN113362990A